IBM SAN Volume Controller Best Practices and Performance Guidelines - Nayak, Anil; Rainero, Antonio; Whyte, Barry; Hoffmann, Chris; Miyasiro, Danilo; Green, David; Bolland, Duane; Shea, Jackson; Herd, Jon; Fincher, Jordan; Avalos, Marcelo; Kubin, Sergey; et al. (IBM Redbooks, 2021)
This IBM® Redbooks® publication describes several of the preferred practices and describes the performance gains that can be achieved by implementing the IBM SAN Volume Controller powered by IBM Spectrum® Virtualize V8.4. These practices are based on field experience. This book highlights configuration guidelines and preferred practices for the storage area network (SAN) topology, clustered system, back-end storage, storage pools, and managed disks, volumes, Remote Copy services, and hosts. Then, it provides performance guidelines for IBM SAN Volume Controller, back-end storage, and applications. It explains how you can optimize disk performance with the IBM System Storage Easy Tier® function. It also provides preferred practices for monitoring, maintaining, and troubleshooting IBM SAN Volume Controller. This book is intended for experienced storage, SAN, and IBM SAN Volume Controller administrators and technicians. Understanding this book requires advanced knowledge of the IBM SAN Volume Controller, IBM FlashSystem, and SAN environments.
Online resource; Title from title page (viewed May 6, 2021)